Examining Biogas Potential from Rotting Fruits for Advanced Waste Management, Environmental Conservation, and Sustainable Energy Generation - Tian Adhia Nugraha; Annisa Rahmawati (The Journal of Indonesia Sustainable Development Planning, 2023)
This research aims to analyze the efforts of Koperasi Gemah Ripah Yogyakarta in converting rotting fruits into biogas as part of waste management at Gamping Fruit Market. The methodology involved interviews, field studies, and a comprehensive literature review from various journals. The research findings are threefold. Firstly, Koperasi Gemah Ripah employs a systematic approach to waste management comprising collection, transportation, and disposal. Secondly, the biogas produced through the processing efforts made by Koperasi Gemah Ripah serves as an alternative energy source, generating electricity. Thirdly, the collaborative partnership between Koperasi Gemah Ripah and the Waste Refinery Center at Universitas Gadjah Mada has been proven to be successful in innovatively managing waste by converting it into biogas. In conclusion, the research underscores the effective waste management strategies implemented by Koperasi Gemah Ripah, showcasing the potential of biogas as a sustainable solution to mitigate environmental damage.